Caudal Approach to Laparoscopic Liver Resection—Conceptual Benefits for Repeated Multimodal Treatment for Hepatocellular Carcinoma and Extended Right Posterior Sectionectomy in the Left Lateral Position - Endo, Tomoyoshi; Morise, Zenichi; Katsuno, Hidetoshi; Kikuchi, Kenji; Matsuo, Kazuhiro; Asano, Yukio; Horiguchi, Akihiko (Frontiers in Oncology, 2022)
We had reported the novel concept of “caudal approach in laparoscopic liver resection” in 2013. In the first report, caudal approach of laparoscopic transection-first-posterior sectionectomy without prior mobilization of the liver in left lateral position was described. Thereafter, 10 complex laparoscopic extended posterior sectionectomies with combined resection of right hepatic vein or diaphragm were performed using the same approach. In present study, the short-term outcomes of those cases and 42 cases of laparoscopic sectionectomies or hemi-hepatectomies (excluding left lateral sectionectomy) were compared. There was no statistically significant difference between the groups in sex, age, diseases for resection, preoperative liver function, tumor number and size, and, also as outcomes, operation time, intraoperative blood loss, morbidity, conversion to laparotomy and post-operative hospital stay. Even complex laparoscopic extended posterior sectionectomy was performed safely using the procedure. This approach has the technical benefits of acquisition of well-opened transection plane between resected liver fixed to the retroperitoneum and residual liver sinking down to left with the force of gravity during parenchymal transection, and less bleeding from right hepatic vein due to its higher position than IVC. Furthermore, it has an oncological benefit like the anterior approach in open liver resection, even in posterior sectionectomy. The detailed procedure and general conceptual benefits of caudal approach to laparoscopic liver resection for repeated multimodal treatment for hepatocellular carcinoma were also described.